امكانية تخفيض التكاليف الثابتة للحكومات الليبية المتعاقبة (Comprehensive Journal of Science, 2025)
This research paper addresses the critical issue of the growing structural burden of fixed costs (salaries, wages, and subsidies) within the successive budgets of Libyan governments, and evaluates the feasibility of reducing this burden to ensure fiscal sustainability and achieve development. The study reveals that public spending in Libya is characterized by unprecedented fiscal rigidity resulting from the dominance of fixed costs, which account for over three-quarters of total expenditure in certain years. This leads to the complete crowding out of developmental spending and the depletion of national wealth without any significant metric for efficiency or productivity.The study confirms that the root cause of this inflation lies in the application of Rentier Economy policies, which rely on excessive public sector employment (disguised unemployment) and the provision of untargeted blanket commodity subsidies as tools for maintaining social peace. This approach generates immense waste and economic distortions. Based on theoretical and methodological analysis, the paper concludes that reducing these costs is both possible and urgent, requiring the adoption of a comprehensive structural reform focused on two main pillars: the gradual transition to targeted cash subsidies to compensate citizens and achieve immediate fiscal savings, and the restructuring of the wage bill through database cleansing and unified schedules to link compensation with productivity.The recommendations emphasize that the success of these reforms is contingent upon unified political will, transparent financial disclosure, and inclusive social dialogue, ensuring a smooth transition from the unproductive rentier spending model to an efficient and sustainable fiscal framework.
Keywords: Fixed Costs, Libyan Public Finance, Expenditure Rationalization, Rentier Economy, Subsidy Reform, Targeted Cash Subsidies, Wage Restructuring, Successive Libyan Governments.